An Analysis of Politeness Strategy Used by The Actors of Johnny English Film and Its Translation - Esriaty Sega' Kendenan (Universitas Teknokrat Indonesia, 2023)
This study aims at examining politeness strategies in the utterances of actors and actresses in the Johnny English film and determine the accuracy of the translation both grammatically and pragmatically using two versions of fansub translations. The data sources of this research are in the form of Source Text (ST) taken from the Johnny English film subtitles as well as its two translated versions (TT) by two fansubs which are downloaded from the subscene. Data analysis was carried out by comparing the two versions of TT with the TS to determine and assess the politeness strategies of the actors, as well as how the fansubs translate speech acts with these politeness strategies descriptively. From the analysis of the data, it was found that in general there is a cross-strategy combination between different types of politeness, not in the same type of politeness, in each speech act. In addition, this study also reveals that the two translated versions of the two fansubs selected in this study can generally produce surface-accurate translations, but do not always produce the same politeness effect.Keywords: Fansub, Johnny English, politeness strategy, speech acts, translation